COMPARATIVE ANALYTICAL DETERMINATION OF THERMAL PROTECTION BEHAVIOR FOR EXPERIMENTAL MODELS MADE OF STRATIFIED BIOCOMPOSITE BOARDS OF LIGNO-CELLULOSE NATURE - SILVIA - ANDREEA NITU; RADU I. IATAN; ION DURBACA; GABRIEL PETROSEL; ELENA SURDU; DANA CLAUDIA FARCAS - FLAMAROPOL (Journal of Engineering Studies and Research)
The paper addresses the comparative analytical determination of thermal insulation behavior for various experimental models made of stratified and hybrid biocomposites of ligno-cellulose nature. The analytical determination of the thermal resistance and the overall thermal insulation coefficient for each experimental model is performed using the calculation methodology for energy efficiency. The results obtained after the analysis of the thermal insulation behavior for the biocomposite panels highlighted the fact that they have thermal insulation properties with high values for thermal resistance and global thermal insulation coefficients.